Engaging young people and their caregivers in support services following harmful sexual behaviors: Qualitative analysis. (May 2023) - Kor, Kenny; Hanley, Natalia; Fabrianesi, Belinda; Simpson, Helen; Finlay, Summer May; Spangaro, Jo; Allan, Julaine; Payne, Jason
Abstract: Background: Harmful sexual behavior (HSB) displayed by children and young people under the age of 18 has been described as developmentally inappropriate, may be harmful towards self or others, or be abusive towards another child, young person, or adult. Early intervention and treatment completion are crucial to cease HSB, reduce impacts and address underlying issues for the child who has displayed HSB. Considerable shame attaches to seeking help for this stigmatized behavior which may result in dropout from support services. Understanding young people and caregivers' experiences of what facilitates or hinders their engagement with support services is therefore critical to preventing re-occurrence of HSB and keeping children safe. Objective: This article draws on the first-hand experience of young people and caregivers to address the question: What have they found helpful and unhelpful when engaging with services for harmful sexual behavior? Participants and setting: Participants were recruited from public health and youth justice services in the state of New South Wales, Australia. The 31 participants included 11 young people (aged 14 to 17) and 20 caregivers (parents, foster or kinship carers). Methods: Qualitative data were collected through individual semi-structured interviews, following which thematic analysis was conducted. Results: Data analysis identified three helpful responses: (1) non-judgmental recognition of crisis; (2) child-centred and family-focused orientation; and (3) multi-dimensional interventions. Unhelpful responses included: (1) closed doors (an inability to access a service) (2) stigmatization of HSB; and (3) reduced caregivers' autonomy. Conclusions: Greater involvement of caregivers, non-stigmatizing language and coordinated responses between generalist and specialist services are needed to facilitate service engagement.